Learning the lessons of WannaCry. Issue 9 (September 2018) - Adams, Chris
Abstract : It was May 2017 when the ransomware attack WannaCry made headlines around the world. The virus brought unprecedented attention to malicious software-based threats that don't just infect technology systems but also demand money.